VP8, the Major Tegument Protein of Bovine Herpesvirus 1, Interacts with Cellular STAT1 and Inhibits Interferon Beta Signaling - Afroz, Sharmin (J Virol, 2016)
The U(L)47 gene product, VP8, is the most abundant tegument protein of bovine herpesvirus 1 (BoHV-1). Previously, we demonstrated that a U(L)47-deleted BoHV-1 mutant (BoHV1-ΔU(L)47) exhibits 100-fold-reduced virulence in vitro and is avirulent in vivo. In this study, we demonstrated that VP8 expression or BoHV-1 infection inhibits interferon beta (IFN-β) signaling by using an IFN-α/β-responsive plasmid in a luciferase assay. As transducer and activator of transcription (STAT) is an essential component in the IFN-signaling pathways, the effect of VP8 on STAT was investigated. An interaction between VP8 and STAT1 was established by coimmunoprecipitation assays in both VP8-transfected and BoHV-1-infected cells. Two domains of VP8, amino acids 259 to 482 and 632 to 686, were found to be responsible for its interaction with STAT1. The expression of VP8 did not induce STAT1 ubiquitination or degradation. Moreover, VP8 did not reduce STAT1 tyrosine phosphorylation to downregulate IFN-β signaling. However, the expression of VP8 or a version of VP8 (amino acids 219 to 741) that contains the STAT1-interacting domains but not the nuclear localization signal prevented nuclear accumulation of STAT1. Inhibition of nuclear accumulation of STAT1 also occurred during BoHV-1 infection, while nuclear translocation of STAT1 was observed in BoHV1-ΔU(L)47-infected cells. During BoHV-1 infection, VP8 was detected in the cytoplasm at 2 h postinfection without any de novo protein synthesis, at which time STAT1 was already retained in the cytoplasm. These results suggest that viral VP8 downregulates IFN-β signaling early during infection, thus playing a role in overcoming the antiviral response of BoHV-1-infected cells. IMPORTANCE Since VP8 is the most abundant protein in BoHV-1 virions and thus may be released in large amounts into the host cell immediately upon infection, we proposed that it might have a function in the establishment of conditions suitable for viral replication. Indeed, while nonessential in vitro, it is critical for BoHV-1 replication in vivo. In this study, we determined that VP8 plays a role in downregulation of the antiviral host response by inhibiting IFN-β signaling. VP8 interacted with and prevented nuclear accumulation of STAT1 at 2 h postinfection in the absence of de novo viral protein synthesis. Two domains of VP8, amino acids 259 to 482 and 632 to 686, were found to be responsible for this interaction. These results provide a new functional role for VP8 in BoHV-1 infection and a potential explanation for the lack of viral replication of the U(L)47 deletion mutant in cattle.